Revitalisation Initiatives: The Enhancement Of Cultural Heritage In Greater Resistencia - Schneider, Valeria (International Journal of Built Environment and Scientific Research, 2017)
This paper explores the urban planning initiatives in revitalisation as usefull approach for intervention in derelict areas and buildings who had important role in the past and the government decided to restore for cultural and social purposes. Revitalisation policies tend to address urban growth within built-up cores by enhancing historical areas and derelict areas and neighborhoods. Meanwhile, urban expansion tends to be related to either suburban growth in developed regions or informal settlements in developing countries. Within the last forty years, city councils in all regions have needed to address urban issues with ever tighter budgets and so they do experience similar problems, particularly in relation to planning issues. Greater Resistencia, a city located in one of the poorest region within Argentina, was always been supported by National Government, is not exception to this rule. These initiatives can be seen as starting point to fuelled local economy and reduced dependence from National Government. This paper will explore one of the urban revitalization initiatives currently applying in Greater Resistencia (Argentina) and attempts to analyze the achievement and failures, assessing them, by taking examples in Resistencia and recent experiences in Preston (UK).